Proceedings of the IEEE 2009 National Aerospace &Amp; Electronics Conference (NAECON) 2009
DOI: 10.1109/naecon.2009.5426617
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus generator for SEIR method based ADC BIST

Abstract: Testing of ADC in SOC is a significant challenge since it usually has no connection to the outside. Built-in self-test (BIST) is regarded as a promising alternative to traditional test. Most reported ADC BIST research works try to replicate a production test scheme on chip. This approach requires input ramp with high linearity which is hard to achieve on chip. This paper investigates signal generator implementation issues of adapting stimulus error identification and removal method which was presented for prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…will be slightly smaller but the conclusion in (5.12) and (5.13) are still valid. (54) and (70), the shift generators are independent, but the structure of the BIST is relatively more complicated, consuming more power and requiring more design efforts. To eliminate the dependency on the ADC architecture, an independent low-power shift generator with simple structure is a better choice for on-chip implementation.…”
Section: So For the Last Bit (Bit N-1) The Impedance Looking Into Tmentioning
confidence: 99%
“…will be slightly smaller but the conclusion in (5.12) and (5.13) are still valid. (54) and (70), the shift generators are independent, but the structure of the BIST is relatively more complicated, consuming more power and requiring more design efforts. To eliminate the dependency on the ADC architecture, an independent low-power shift generator with simple structure is a better choice for on-chip implementation.…”
Section: So For the Last Bit (Bit N-1) The Impedance Looking Into Tmentioning
confidence: 99%
“…Two sets of histogram counts, C 1 and C 2 , , are obtained from R 1 and R 2 respectively. For a detailed working of the algorithms refer to [3] and [4].Simple signal generators described in [7] can be used to generate the stimuli.…”
Section: B Stimulus For the Seir And Khk Algorithmmentioning
confidence: 99%
“…The low linearity stimulus used for simulations is 7-bit linear, generated from simulations of signal generator circuit suggested in [7]. The ADC that has been used for simulation is a 14-bit flash type ADC.…”
Section: Simulation Conditionsmentioning
confidence: 99%
“…For FRE based SEIR testing used in this work, it can be shown that for a small shift, the algorithmic error in estimating the INL of the ADC will be bounded by 0.25LSB if the following condition [4] is satisfied:…”
Section: Constancy Requirementmentioning
confidence: 99%
“…The challenge of generating highly linear or spectrally pure stimulus signals with a very small die area is one of the biggest challenges in developing practical methods for Built in Self Test (BIST) of ADCs [4]- [5]. For this reason, quasi static linearity BIST of even a 12-bit ADC is almost never attempted in commercial products.…”
Section: Introductionmentioning
confidence: 99%